Anti‐inflammatory effects of hypoxia‐preconditioned human periodontal ligament cell secretome in an experimental model of multiple sclerosis: a key role of IL‐37. Issue 12 (23rd August 2017) - Giacoppo, Sabrina; Thangavelu, Soundara Rajan; Diomede, Francesca; Bramanti, Placido; Conti, Pio; Trubiani, Oriana; Mazzon, Emanuela
ABSTRACT: Recent research has widely investigated the anti‐inflammatory effects of mesenchymal stem cells and their secretory products, termed the secretome, in the treatment of multiple sclerosis (MS). The present study examined the capacity of the conditioned medium (CM) from human periodontal ligament stem cells (hPLSCs) under hypoxia (H‐hPDLSCs‐CM) to suppress experimental autoimmune encephalomyelitis (EAE), a murine model of MS. To induce EAE, female C57BL/6 mice were immunized with myelin oligodendroglial glycoprotein peptide35–55 . At the onset of symptoms, H‐hPDLSCs‐CM was infused via the tail vein of mice. Our results demonstrate the efficacy of H‐hPDLSCs‐CM treatment in diminishing clinical and histologic disease score. A key finding from this study is the marked expression of anti‐inflammatory cytokine IL‐37, paralleled by the suppression of proinflammatory cytokines in mice with EAE that were treated with H‐hPDLSCs‐CM. In addition, a consequent modulation of oxidative stress, autophagic, and apoptotic markers was observed in mice with EAE after hPDLSCs‐CM administration. In addition, to provide additional evidence of the molecular mechanisms that underlie H‐hPDLSCs‐CM, we investigated its therapeutic action in scratch injury–exposed NSC‐34 neurons, an in vitro model of injury. This model reproduces severe inflammation and oxidative stress conditions as observed after EAE damage. In vitro results corroborate the ability of hPDLSCs‐CM to modulate inflammatory, oxidative stress, and apoptotic pathways. Taken together, our findings suggest H‐hPDLSCs‐CM as a new pharmacologic opportunity for the management of MS.—Giacoppo, S., Thangavelu, S. R., Diomede, F., Bramanti, P., Conti, P., Trubiani, O., Mazzon, E. Anti‐inflammatory effects of hypoxia‐preconditioned human periodontal ligament cell secretome in an experimental model of multiple sclerosis: a key role of IL‐37. FASEB J. 31, 5592–5608 (2017). www.fasebj.org